1990
DOI: 10.1002/cne.903000407
|View full text |Cite
|
Sign up to set email alerts
|

The mechanoreceptive origin of insect tympanal organs: A comparative study of similar nerves in tympanate and atympanate moths

Abstract: A chordotonal organ occurring in the posterior metathorax of an atympanate moth, Actias luna (L.) (Bombycoidea: Saturniidae), appears to be homologous to the tympanal organ of the noctuoid moth. The peripheral anatomy of the metathoracic nerve branch, IIIN1b1 was examined in Actias luna with cobalt-lysine and Janus Green B, and compared to its counterpart, IIIN1b (the tympanal branch), in Feltia heralis (Grt.) (Noctuoidea: Noctuidae). The peripheral projections of IIIN1b1 were found to be similar in both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…The first reports of the B cell in noctuoid moths discounted its role as an auditory receptor (Roeder and Treat, 1957;Treat and Roeder, 1959) and this conclusion has been supported in subsequent studies (Surlykke, 1984;Yack and Fullard, 1990). Lechtenberg (1971), however, observed that the firing of the B cell in a number of North American noctuids, including one used in our study, Leucania pseudargyria, was inhibited by pulsed ultrasonic stimuli.…”
Section: B Cellsupporting
confidence: 82%
See 1 more Smart Citation
“…The first reports of the B cell in noctuoid moths discounted its role as an auditory receptor (Roeder and Treat, 1957;Treat and Roeder, 1959) and this conclusion has been supported in subsequent studies (Surlykke, 1984;Yack and Fullard, 1990). Lechtenberg (1971), however, observed that the firing of the B cell in a number of North American noctuids, including one used in our study, Leucania pseudargyria, was inhibited by pulsed ultrasonic stimuli.…”
Section: B Cellsupporting
confidence: 82%
“…It is unlikely, however, that these responses play any role in the natural avoidance behaviour of the flying moth since the acoustic conditions required to elicit them would not be encountered in an attacking bat. It has been suggested that the B cell in noctuoid moths is the evolutionary vestige of a homologous proprioceptor in thoracically earless moths (Treat and Roeder, 1959;Yack and Fullard, 1990). We suggest that its persistence in eared noctuid moths is simply a reflection of the low evolutionary 'cost' that simple nervous sensory systems present to their owners, e.g.…”
Section: B Cellmentioning
confidence: 72%
“…Histological and genetic analysis revealed no general di¡erence between scolopidial units of the various sense organs responding to the di¡erent stimuli. Mainly based on the segmental arrangement and embryonic development of the scolopidial organs, it has been postulated that insect ears have evolved from proprioceptive organs (Boyan 1993(Boyan , 1998Fullard & Yack 1993;Meier & Reichert 1990;Yack & Fullard 1990). Recent functional analysis revealed that unspecialized scolopidial organs may also react to airborne sound and that specialization increases the sensitivity resulting in a tympanate ear (Shaw 1994a,b;Van Staaden & Ro« mer 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The auditory neurons have different thresholds, with A1 being approximately 20 dB SPL more sensitive than A2 (Boyan and Fullard, 1986). The third neuron's role is unclear; this neuron is a homolog to a neuron in atympanate moths that is responsible for proprioception of the wing position (Hasenfuss, 1997;Yack and Fullard, 1990;Yack et al, 1999). Previous work has shown that with free-flying atympanate moths, in the wing up position the B cell fires rapidly while in the wing down position it fires more slowly (Yack and Fullard, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…The auditory neurons directly attach to the inside of the tympanal membrane (Fig. 1A,B) and then join with the B cell in the adjoining air sac, creating the auditory nerve (Treat and Roeder, 1959;Yack and Fullard, 1990). The auditory nerve then travels through muscle tissue before eventually reaching the pterothoracic ganglion (Fig.…”
Section: Introductionmentioning
confidence: 99%